Implementasi IMPLEMENTASI PENERAPAN HUKUMAN KEBIRI KIMIAWI TERKAIT KEPENTINGAN KORBAN DAN FUNGSI PEMIDANAAN :: TELAAH PERBANDINGAN NEGARA INDONESIA- AMERIKA SERIKAT - Dian Simanjuntak Narwastuty (Dialogia Iuridica, 2024)
Sexual crimes are a form of crime that is rife today. This can arise due to imbalances in the role of community oversight, weaknesses in law enforcement, and misuse of technology among the younger generation. It has transformed a form of conventional sexual crime into a modern sexual crime involving advanced technology and complicated syndicates. On the side of victims of sexual crimes, special handling is needed to solve sexual crime cases.  On the side of victims of sexual crimes, special handling is needed to solve sexual crime cases. This is done in the pattern of examination, submission of evidence, determination of suspects, even for trials that are carried out specifically. The victim needs to be protected, so a chemical castration is required. This study uses descriptive analysis methods for a number of regulations applicable in Criminal Law and Criminal Procedure Law. This research is also complemented by a literature approach in the form of Indonesian legal literature and legal journals to provide support for the implementation of chemical castration for sexual crimes. This paper shows that the Indonesian government should immediately impose chemical castration penalties against child predators. The Indonesian government must also ensure the certainty of the rights of children who are victims of child predators through chemical castration.